Subcutaneous birch pollen allergen immunotherapy with a depigmented polymerized extract shows only sustained and long‐term efficacy in a subgroup of monosensitized adults and adolescents with allergic rhinitis. Issue 10 (5th October 2022) - Novak, Natalija; Worm, Margitta; Staubach, Petra; Jutel, Marek; Sager, Angelika; Pfaar, Oliver
Abstract: Background: Allergen immunotherapy (AIT) is an approved treatment for seasonal respiratory allergic diseases. A depigmented polymerized birch pollen extract for subcutaneous allergen immunotherapy (SCIT) has been demonstrated to be efficacious and safe in patients allergic to birch pollen and its homologous group. Objective: To determine whether SCIT with a birch pollen formulation (5000 depigmented polymerized (DPP) units/mL) shows sustained and long‐term efficacy in adults and adolescents with birch‐pollen induced allergic rhinitis with or without intermittent asthma. Methods: A multicentre ( n = 66), double‐blind, placebo‐controlled Phase III clinical trial was performed in the Czech Republic, Finland, Germany, Latvia, Lithuania, Poland and Russia. Participants were randomized 2:1 to active treatment (birch 5000 DPP/ml) or placebo for three years of SCIT and followed up for two treatment‐free years. The primary efficacy endpoint was the EAACI's combined symptom and medication score for rhinoconjunctivitis (CSMSEAACI ). Results: A total of 973 participants were screened and 649 were randomized (active treatment: n = 434; placebo: n = 215). The intention‐to‐treat analysis of the CSMSEAACI in the overall study population did not demonstrate statistically significant differences in years 1, 2 and 3. In a post‐hoc analysis, among the subgroup of patients monosensitized to birch pollen allergen only ( n = 200), we observed a statistically significant difference (active treatment vs. placebo) in the CSMSEAACI in year 2, 3 and 5. The AIT's safety profile was good. Conclusions: SCIT with a depigmented polymerized birch pollen extract was safe. Sustained and long‐term efficacy in years 2, 3 and 5 in monosensitized patients, but not in polysensitized patients was demonstrated. (EudraCT 2012‐000414‐11)